1997
DOI: 10.1172/jci119530
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor genotype is associated with radiographic osteoarthritis at the knee.

Abstract: Osteoporosis and osteoarthritis are age-related disorders of the skeleton with genetic components. Low bone density is a risk factor for osteoporotic fracture while osteoarthritis is associated with increased bone density. The 1,25-dihydroxyvitamin D 3 receptor (VDR) gene locus was previously found to be associated with bone density. We therefore studied the relationship between radiographic osteoarthritis at the knee and VDR genotype in a population-based sample ( n ϭ 846), using molecular haplotyping of anon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 33 publications
5
76
1
6
Order By: Relevance
“…The true pathogenesis of OA resides in degeneration and subsequent loss of articular cartilage, however; osteophytes only reflect the reactive change. The dominance of osteophytes in diagnosing radiographic OA using the Kellgren scale has been pointed out (Hart and Spector 1995;Uitterlinden et al 1997). In contrast, our new three-part scale emphasizes joint-space narrowing and estimates the severity of osteophytes independently.…”
Section: Sample Collectionmentioning
confidence: 89%
“…The true pathogenesis of OA resides in degeneration and subsequent loss of articular cartilage, however; osteophytes only reflect the reactive change. The dominance of osteophytes in diagnosing radiographic OA using the Kellgren scale has been pointed out (Hart and Spector 1995;Uitterlinden et al 1997). In contrast, our new three-part scale emphasizes joint-space narrowing and estimates the severity of osteophytes independently.…”
Section: Sample Collectionmentioning
confidence: 89%
“…[21] However, in a study of sporadic prostate cancer in the Turkish population, [22] the VDR gene ApaI polymorphism was found to be associated with the disease. Although, VDR gene polymorphisms were discovered to be associated with hand OA in Finnish women [10] and with radiographic OA in Netherlands, [8] Huang et al [11] did not find any association between VDR gene polymorphisms and hand, hip or knee OA in a Japanese population. This finding is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants of the VDR gene locus on chromosome 12 are associated with bone density, which was found to increase in patients with OA. [8] Nonetheless, it is still uncertain whether genetic variants of the VDR gene (TaqI and ApaI polymorphisms) are involved in the development of OA. [9][10][11] Since gene pools, lifestyle, and geneenvironment interactions vary between populations, the risk should not be the same with respect to genotypes in every population.…”
mentioning
confidence: 99%
“…These genes have been studied in OA, but VDR has received the most attention, and first reports have shown significant associations with an increased risk in the presence of different polymorphisms (Ken et al, 1997;Uitterlinden et al, 1997;Solovieva et al, 2006;Valdes et al, 2006); however, this has not always been confirmed (Aerssens et al, 1998;Baldwin et al, 2002;Huang et al, 2000;Loughlin et al, 2000b). A meta-analysis on the most frequently studied VDR polymorphisms (TaqI, BsmI, and ApaI) in OA analyzed a total of 10 studies of persons of Asian or European origin involving a total of 1,591 patients with OA and 1,781 controls.…”
Section: Modulation Of Osteocyte or Chondrocyte Differentiationmentioning
confidence: 99%